Bacteriostatic absorption core and preparation method thereof

By using modified PET fibers and dopamine hydrochloride (DA) in the antibacterial absorption core, the existing antibacterial absorption core does not have anticoagulant function and great cytotoxicity, achieving efficient and long-lasting antibacterial effect and good biocompatibility.

CN119656359AActive Publication Date: 2025-03-21FUJIAN HENGAN HLDG CO LTD +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411836195.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing antibacterial absorption core does not have anticoagulant function, and the method of coating and adding Ag+ leads to greater cytotoxicity or coating and adding Ag+ leads to relatively poor antibacterial effect.

Method used

Using an antibacterial absorption core, including a lower non-woven fabric layer, a SAP and modified PET fiber mixture layer, a glue-sizing layer and an upper non-woven fabric layer arranged from bottom to top, the modified PET fibers form a double helix structure through twisting treatment, combining the reaction of dopamine hydrochloride (DA) and silver ammonia solution to form a polydopamine (PDA) and silver ion complex, enhancing antibacterial and anticoagulation properties.

Benefits of technology

It achieves stability and durability of antibacterial effects, and also has anticoagulant functions, reduces the risk of cytotoxicity, and improves the biocompatibility and absorption efficiency of the core.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656359A_ABST
    Figure CN119656359A_ABST
Patent Text Reader

Abstract

The invention relates to the field of hygienic products, provides a bacteriostatic absorption core body and a preparation method thereof, and solves the problems that an existing bacteriostatic absorption core body does not have an anticoagulation function, and Ag < + > is easy to migrate to a human body in a manner of coating and adding Ag < + > or the bacteriostatic effect is relatively poor in a manner of coating and adding Ag < + >. The antibacterial absorption core body comprises a lower non-woven fabric layer, an SAP and modified PET fiber mixture layer, a sizing layer and an upper non-woven fabric layer which are sequentially laminated from bottom to top; wherein the SAP and modified PET fiber mixture layer is obtained by mixing SAP and modified PET fibers and then carrying out negative pressure adsorption, conveying and forming, and the modified PET fibers comprise the following raw materials: acetone, absolute ethyl alcohol, PET fibers, sodium periodate, dopamine hydrochloride, N, N-dimethylformamide, propylene glycol monomethyl ether, a silver ammonia solution, azodiol enamine, hydrochloric acid, N, N-dimethylformamide and deionized water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sanitary products, and in particular to an antibacterial absorption core and a preparation method thereof. Background Art

[0002] Sanitary napkins are sanitary products designed for women to use during their menstrual period. Their core function is to absorb menstrual blood and keep the private parts dry. With the advancement of science and technology, the design and materials of sanitary napkins are constantly being innovated and improved to enhance the comfort of users and the functionality of the products. Among the many improvements, an important direction is to enhance the antibacterial function of sanitary napkins. Sanitary napkins can easily become a breeding ground for bacteria during women's menstrual period, because menstrual blood contains rich nutrients, and the warm and humid environment of the private parts provides suitable conditions for the growth of bacteria. This function is mainly achieved by adding substances with antibacterial properties to sanitary napkins. These substances can effectively reduce the growth of bacteria, thereby reducing the risk of infection for users. Although some sanitary napkins claim to have antibacterial effects, the actual effect may vary from product to product. Some products may not provide sufficient antibacterial protection, or the antibacterial ingredients may cause allergic reactions in some women.

[0003] Metal ions have antibacterial effects on a variety of bacteria, fungi, and viruses. They are a broad-spectrum antibacterial agent with a long-lasting antibacterial effect. Even after long-term use, they can still maintain a certain antibacterial activity. Silver ions have low toxicity to human cells and will not damage normal cells. Therefore, they are safer and are widely used in water treatment, skin care products, daily necessities, medical equipment and other fields. For example, the antibacterial sanitary napkins launched by the international brand Kao claim to use a silver ion antibacterial system.

[0004] There are generally two ways to add existing silver ion materials. One is to apply a silver ion antibacterial finishing agent after the fiber material is formed. The other is to load silver ions or silver nanoparticles onto different substrates to form a composite material to form an antibacterial masterbatch, which is then mixed into the fiber as a functional masterbatch during fiber forming. The former treatment method is dissolution-based antibacterial. If silver ions migrate into the human body and are excessively used over a long period of time or repeatedly, the pH value in the human body may increase, causing electrolyte disorders. In addition, some people may be allergic to silver ions and experience allergic symptoms such as skin redness, swelling, and itching. The latter treatment method is non-dissolution-based antibacterial. Silver ions or other metal ions cannot fully function when coated in the fiber, and a higher amount of addition is required. In addition, there may still be dissolution problems in actual applications.

[0005] Chinese patent application No. 202011636229.6 discloses a high-efficiency, fast-acting, non-dissolving antibacterial composite fiber and its preparation method, which is an ES sheath-core composite fiber, the sheath contains PE non-metallic doped zinc oxide semiconductor antibacterial masterbatch, and the core contains PET or PP metal-doped zinc oxide semiconductor antibacterial masterbatch; the two masterbatches are added to the side feeding pipes of the sheath and core melt pipes respectively, and then extruded by a twin-screw extruder, and then sprayed out through a composite spinneret assembly, cooled, formed, oiled, and wound, stretched, curled, and shaped to obtain a high-efficiency, fast-acting, non-dissolving antibacterial composite fiber with good physical properties. However, the fiber requires a higher amount of antibacterial ion addition, and its antibacterial effect is relatively poor when the same amount of antibacterial ion addition is used.

[0006] Chinese patent application No. 202210238576.6 discloses a nanosilver antibacterial sanitary napkin, which is composed of a surface layer, a nanosilver chip, an absorption layer, a bottom film, a release paper layer, a coating and a quick-release sticker stacked together from top to bottom. The nanosilver chip is obtained by treating the non-woven fabric with antibacterial finishing and hydrophilic finishing respectively. Compared with the prior art, the invention uses cocoa bean shells, a by-product discarded in the processing of cocoa powder, as raw materials, which reduces waste and expands the application field of cocoa bean shells; cocoa bean shell extract has good antibacterial and antioxidant effects, and can reduce silver ions into nanosilver particles, which together with nanosilver particles in the sanitary napkin play an excellent antibacterial property. However, the sanitary napkin of the invention does not have anticoagulant function, and the adhesion of the antibacterial finishing liquid on the surface of the non-woven fabric is relatively poor. Summary of the invention

[0007] Therefore, in view of the above problems, the present invention provides an antibacterial absorbent core and a preparation method thereof, which solves the problem that the existing antibacterial absorbent core does not have anticoagulant function and is coated with Ag. + The method leads to greater cytotoxicity or coating with Ag + The method leads to the problem of relatively poor antibacterial effect.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] The invention discloses an antibacterial absorption core, comprising a lower non-woven fabric layer, a SAP and modified PET fiber mixture layer, a sizing layer and an upper non-woven fabric layer which are sequentially stacked from bottom to top; wherein the SAP and modified PET fiber mixture layer is obtained by negative pressure adsorption, conveying and molding of SAP and modified PET fibers, and the modified PET fibers comprise the following raw materials: acetone, anhydrous ethanol, PET fibers, sodium periodate, dopamine hydrochloride, N,N-dimethylformamide, propylene glycol methyl ether, silver ammonia solution, azodiol enamine, hydrochloric acid, N,N-dimethylformamide and deionized water.

[0010] Furthermore, the modified PET fiber has a double helix structure.

[0011] Furthermore, the modified PET fibers form a single row with a volume showing a large-small-large structure from top to bottom.

[0012] Furthermore, the SAP is distributed in a staggered manner between the upper and lower adjacent layers of the double helix structure.

[0013] Furthermore, the modified PET fiber is wavy in shape.

[0014] A method for preparing an antibacterial absorbent core comprises the following steps:

[0015] S1. Preparation of P solution: Mix acetone and anhydrous ethanol evenly in a volume ratio of 3-4:1, then add P powder to prepare a P solution with a concentration of 0.1-1 g / ml;

[0016] S2, preparation of modified PET: immerse PET fiber in an ethanol solution with a concentration of 30-45%, ultrasonically treat for 30-45 minutes and then dry, then immerse the dried PET fiber in the P solution obtained in step S1, add 1-5 parts by weight of sodium periodate, stir to react for 1-2 hours, then vacuum dry at 40-45°C for 10-12 hours, pour out the supernatant, and then dry at 100-120°C for 1-2 hours to obtain modified PET;

[0017] S3. Preparation of antibacterial absorption core:

[0018] a. The modified PET obtained in step S2 is twisted to obtain modified PET fibers with a double helix structure, and then the modified PET fibers are arranged in a single row with a volume of large-small-large from top to bottom through auxiliary airflow control, the lower non-woven fabric is unwound and transported, and glue is applied on the upper surface of the lower non-woven fabric;

[0019] b. Mixing the SAP and the modified PET fiber, adsorbing, conveying, and forming the mixture under negative pressure, and then compounding the mixture onto the surface of the lower non-woven fabric;

[0020] c. unwinding and conveying the upper non-woven fabric, applying glue to the lower surface of the upper non-woven fabric, and then laminating the upper non-woven fabric to the product in step b, and obtaining the antibacterial absorption core after cutting;

[0021] Wherein, the preparation method of the P powder is:

[0022] I. Under the protection of high-purity nitrogen, dopamine hydrochloride is added to N, N-dimethylformamide and propylene glycol methyl ether in a solid-liquid ratio of 3-5:20:20, and the mixture is uniformly stirred for 1-2 hours to fully dissolve the dopamine hydrochloride to obtain a first mixed solution;

[0023] II. Add 1-3 parts by weight of silver ammonia solution to the first mixed solution obtained in step I, raise the temperature to 60-70° C., then add 10-15 parts by weight of azodiol enamine, raise the temperature to 100-120° C., and react at a constant temperature for 48-50 hours. After the reaction is completed, a second mixed solution is obtained;

[0024] III. Precipitate the second mixed solution obtained in step II in a hydrochloric acid solution with a pH of 1-1.5, collect the precipitate, dissolve the precipitate in N,N-dimethylformamide, and then precipitate it again in a hydrochloric acid aqueous solution with a pH of 1-1.5, repeat the above process 2-3 times, and then dialyze it with a dialysis bag with a molecular weight cutoff of 3000-3500Da, and then vacuum dry it to obtain P powder.

[0025] Furthermore, the dialysis treatment is: firstly dialysis and purification in N,N-dimethylformamide solution for 72-75 hours, and then dialysis and purification in deionized water for 72-75 hours, and the dialysate is replaced every 6-8 hours.

[0026] Furthermore, the twisting process is: using a jet spinning machine to achieve twisting using high-speed airflow, with a twist of 2500-4500 T·m -1 , the main air flow speed is 50-200m / s, and the auxiliary air flow speed is 10-50m / s.

[0027] Furthermore, the ultrasonic treatment is carried out in an ultrasonic cleaner with an ultrasonic power of 100-120 Hz.

[0028] Furthermore, the modified PET fiber is wavy in shape.

[0029] By adopting the above technical solution, the beneficial effects of the present invention are:

[0030] 1. Dopamine (DA) is a typical catechol compound that can inhibit the growth and reproduction of bacteria. It increases the permeability of bacterial cell membranes, causing the leakage of bacterial intracellular proteins and sugar substances, and disrupting bacterial metabolism. Using dopamine hydrochloride (DA) as the raw material, under the conditions of adding N,N-dimethylformamide and propylene glycol methyl ether, DA self-oxidizes to form polydopamine (PDA); silver ions have antibacterial effects on a variety of bacteria, fungi, and viruses, and are a broad-spectrum antibacterial agent with long-lasting antibacterial effects; the catechol groups rich in PDA produce strong coordination interactions with silver ions, which can construct a stable metal-phenol coordination network, and have a synergistic effect on antibacterial effects, making the antibacterial effect more stable and longer-lasting; and the polyhydroxy structure of PDA itself gives it a certain reducing property, which can convert Ag + Reduce to Ag, avoid Ag + Migrate to the human body and produce cytotoxicity.

[0031] 2. PDA also has super-hydrophilic properties, which can quickly absorb water and form a layer of water molecules on its surface. This layer of water molecules can effectively block the direct contact between proteins and the material surface, thereby reducing the nonspecific adhesion of menstrual blood. At the same time, the catechol groups on PDA form covalent bonds with the electrophilic centers of azodiol enamine (NONOates), achieving chemical bonding, which can achieve anti-coagulation function and improve the absorption efficiency of menstrual blood by the core. When NONOates encounter menstrual blood, they can hydrolyze to generate two molecules of NO, and the release of NO does not depend on specific metabolism or redox reactions. The generation of NO can activate platelets, cause platelet dysfunction, start coagulation cascade reactions, and reduce the level of coagulation factors in the circulation, thereby causing coagulation disorders and maintaining the fluidity of menstrual blood. This mechanism provides an effective anti-coagulation strategy for PDA coatings, enhances the biocompatibility of materials when in contact with menstrual blood, and thus increases the absorption efficiency of SAP for menstrual blood.

[0032] 3. P solution is Ag +A mixed solution is formed after the reaction of NONOates and PDA, that is, a composite in which the effective component of P is Ag / NONOates / PDA. PET fiber is immersed in the P solution, and the abundant catechol functional groups in PDA can spontaneously form hydrogen bonds with the hydroxyl groups on the surface of the PET fiber to achieve strong adhesion on the surface of the PET fiber. Without the introduction of other adhesives, Ag / NONOates / PDA and PET fiber can be firmly bonded, reducing the use of other chemical substances, improving the biocompatibility of the core, and reducing the risk of allergies and irritation. At the same time, the PET fiber adopts stretched deformed yarn, and a wavy microstructure is formed by pre-stretching technology to improve the adhesion of Ag / NONOates / PDA on the surface of the PET fiber. Specifically, in the process of false twisting of the fiber, the yarn is twisted by the interaction between the friction unit and the false twister, and this twist produces a unique curling morphology. In the cooling and shaping stage, the fiber is immersed in the P solution, and the modified PET fiber is obtained after treatment, and its hydrophilicity can meet the absorption requirements and no hydrophilic oil treatment is required.

[0033] 4. The modified PET fiber after twisting has a double helix structure, forming a single row with a large-small-large volume from top to bottom, so that SAP is distributed in a staggered arrangement between the upper and lower adjacent layers, achieving a relatively uniform dispersion, and can be fully absorbed when menstrual blood flows in; the double helix structure can improve the fluffiness and resilience of the core, which helps the rapid penetration and diffusion of menstrual blood, and further improves the absorption efficiency of the core. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a schematic structural diagram of an antibacterial absorbent core in an embodiment of the present invention;

[0035] Explanation of the numbers in the figure: 1- modified PET fiber, 2- SAP. DETAILED DESCRIPTION

[0036] Example 1

[0037] A method for preparing an antibacterial absorbent core comprises the following steps:

[0038] (1) Preparation of P solution

[0039] (1-1) Preparation of P powder

[0040] I. Under the protection of high-purity nitrogen, dopamine hydrochloride is added to N, N-dimethylformamide and propylene glycol methyl ether in a solid-liquid ratio of 3:20:20, and the mixture is uniformly stirred for 1 hour to fully dissolve the dopamine hydrochloride to obtain a first mixed solution;

[0041] II. Add 1 part by weight of silver ammonia solution to the first mixed solution obtained in step I, raise the temperature to 60° C., then add 10 parts by weight of azodiol enamine, raise the temperature to 100° C., and react at a constant temperature for 48 hours to obtain a second mixed solution after the reaction is completed;

[0042] III. Precipitate the second mixed solution obtained in step II in a hydrochloric acid solution with a pH of 1, collect the precipitate, dissolve the precipitate in N,N-dimethylformamide, and then precipitate it again in a hydrochloric acid aqueous solution with a pH of 1, repeat the above process 3 times, and then dialyze it with a dialysis bag with a molecular weight cutoff of 3000Da, first dialyze and purify it in N,N-dimethylformamide solution for 72h, and then dialyze and purify it in deionized water for 72h, replace the dialyzate every 6h, and then vacuum dry it to obtain P powder;

[0043] (1-2) Configuration of P solution

[0044] According to the volume ratio of acetone to anhydrous ethanol being 3:1, acetone and anhydrous ethanol were mixed evenly, and then the P powder was added to prepare a P solution with a concentration of 0.1 g / ml;

[0045] (2) Preparation of modified PET

[0046] The PET fiber is immersed in a 30% ethanol solution, and ultrasonically treated in an ultrasonic cleaner at an ultrasonic power of 100 Hz for 30 min, and then dried. The dried PET fiber is immersed in the P solution obtained in step (1), and 1 part by weight of sodium periodate is added. The reaction is stirred for 1 hour, and then vacuum dried at 40° C. for 10 hours, the supernatant is poured out, and then dried at 100° C. for 1 hour to obtain a modified PET.

[0047] (3) Preparation of antibacterial absorbent core

[0048] (3-1) The modified PET obtained in step (2) is subjected to a twisting treatment to obtain a modified PET fiber having a double helix structure, and then the modified PET fiber is controlled by auxiliary airflow to form a single row with a volume of large-small-large from top to bottom, wherein the twisting treatment is: using an air jet spinning machine to achieve twisting by high-speed airflow, and the twist is 2500 T·m -1 , the main air flow velocity is 50m / s, the auxiliary air flow velocity is 10m / s, the shape of the modified PET fiber is wavy, the lower layer of non-woven fabric is unrolled and conveyed, and glue is applied on the upper surface of the lower layer of non-woven fabric;

[0049] (3-2) mixing the SAP and the modified PET fiber, adsorbing, conveying, and forming the mixture under negative pressure, and then compounding the mixture onto the surface of the lower non-woven fabric;

[0050] (3-3) unwinding and conveying the upper non-woven fabric, applying glue to the lower surface of the upper non-woven fabric, and then compounding the upper non-woven fabric to the product in step (3-2), and obtaining the antibacterial absorbent core after cutting.

[0051] The antibacterial absorption core comprises a lower non-woven fabric layer, a SAP and modified PET fiber mixture layer, a sizing layer and an upper non-woven fabric layer which are stacked in sequence from bottom to top; wherein the SAP and modified PET fiber mixture layer is obtained by negative pressure adsorption, transportation and molding of SAP and modified PET fibers, and the modified PET fibers comprise the following raw materials: acetone, anhydrous ethanol, PET fibers, sodium periodate, dopamine hydrochloride, N,N-dimethylformamide, propylene glycol methyl ether, silver ammonia solution, azodiol enamine, hydrochloric acid, N,N-dimethylformamide and deionized water;

[0052] The modified PET fiber has a double helix structure, and the modified PET fiber forms a single row with a volume of large-small-large from top to bottom. The SAP is distributed in a staggered manner between the upper and lower adjacent layers of the double helix structure, and the modified PET fiber is wavy in shape.

[0053] Example 2

[0054] A method for preparing an antibacterial absorbent core comprises the following steps:

[0055] (1) Preparation of P solution

[0056] (1-1) Preparation of P powder

[0057] I. Under the protection of high-purity nitrogen, dopamine hydrochloride was added to N, N-dimethylformamide and propylene glycol methyl ether in a solid-liquid ratio of 1:5:5, and the mixture was uniformly stirred for 1.5 hours to fully dissolve the dopamine hydrochloride to obtain a first mixed solution;

[0058] II. Add 2 parts by weight of silver ammonia solution to the first mixed solution obtained in step I, raise the temperature to 65° C., then add 12 parts by weight of azodiol enamine, raise the temperature to 110° C., and react at a constant temperature for 49 hours. After the reaction is completed, a second mixed solution is obtained;

[0059] III. Precipitate the second mixed solution obtained in step II in a hydrochloric acid solution with a pH of 1.2, collect the precipitate, dissolve the precipitate in N,N-dimethylformamide, and then precipitate it again in a hydrochloric acid aqueous solution with a pH of 1.2, repeat the above process 3 times, and then dialyze it with a dialysis bag with a molecular weight cutoff of 3200Da, first dialyze and purify it in N,N-dimethylformamide solution for 73 hours, and then dialyze and purify it in deionized water for 73 hours, replace the dialyzate every 7 hours, and then vacuum dry it to obtain P powder;

[0060] (1-2) Configuration of P solution

[0061] According to the volume ratio of acetone to anhydrous ethanol of 3.5:1, acetone and anhydrous ethanol were mixed evenly, and then the P powder was added to prepare a P solution with a concentration of 0.5 g / ml;

[0062] (2) Preparation of modified PET

[0063] The PET fiber is immersed in a 30% ethanol solution, and ultrasonically treated in an ultrasonic cleaner at an ultrasonic power of 110 Hz for 35 min, and then dried. The dried PET fiber is immersed in the P solution obtained in step (1), and 3 parts by weight of sodium periodate is added. The reaction is stirred for 1.5 h, and then vacuum dried at 42° C. for 11 h, the supernatant is poured out, and then dried at 110° C. for 1.5 h to obtain a modified PET.

[0064] (3) Preparation of antibacterial absorbent core

[0065] (3-1) The modified PET obtained in step (2) is subjected to a twisting treatment to obtain a modified PET fiber having a double helix structure, and then the modified PET fiber is controlled by auxiliary airflow to form a single row with a volume of large-small-large from top to bottom, wherein the twisting treatment is: using an air jet spinning machine to achieve twisting by high-speed airflow, and the twist is 3000 T·m -1 , the main air flow velocity is 100m / s, the auxiliary air flow velocity is 30m / s, the shape of the modified PET fiber is wavy, the lower layer of non-woven fabric is unrolled and transported, and glue is applied on the upper surface of the lower layer of non-woven fabric;

[0066] (3-2) mixing the SAP and the modified PET fiber, adsorbing, conveying, and forming the mixture under negative pressure, and then compounding the mixture onto the surface of the lower non-woven fabric;

[0067] (3-3) unwinding and conveying the upper non-woven fabric, applying glue to the lower surface of the upper non-woven fabric, and then compounding the upper non-woven fabric to the product in step (3-2), and obtaining the antibacterial absorbent core after cutting.

[0068] The antibacterial absorption core comprises a lower non-woven fabric layer, a SAP and modified PET fiber mixture layer, a sizing layer and an upper non-woven fabric layer which are stacked in sequence from bottom to top; wherein the SAP and modified PET fiber mixture layer is obtained by negative pressure adsorption, transportation and molding of SAP and modified PET fibers, and the modified PET fibers comprise the following raw materials: acetone, anhydrous ethanol, PET fibers, sodium periodate, dopamine hydrochloride, N,N-dimethylformamide, propylene glycol methyl ether, silver ammonia solution, azodiol enamine, hydrochloric acid, N,N-dimethylformamide and deionized water;

[0069] The modified PET fiber has a double helix structure, and the modified PET fiber forms a single row with a volume of large-small-large from top to bottom. The SAP is distributed in a staggered manner between the upper and lower adjacent layers of the double helix structure, and the modified PET fiber is wavy in shape.

[0070] Example 3

[0071] A method for preparing an antibacterial absorbent core comprises the following steps:

[0072] (1) Preparation of P solution

[0073] (1-1) Preparation of P powder

[0074] I. Under the protection of high-purity nitrogen, dopamine hydrochloride is added to N, N-dimethylformamide and propylene glycol methyl ether in a solid-liquid ratio of 1:4:4, and the mixture is uniformly stirred for 2 hours to fully dissolve the dopamine hydrochloride to obtain a first mixed solution;

[0075] II. Add 3 parts by weight of silver ammonia solution to the first mixed solution obtained in step I, raise the temperature to 70° C., then add 15 parts by weight of azodiol enamine, raise the temperature to 120° C., and react at a constant temperature for 50 hours. After the reaction is completed, a second mixed solution is obtained;

[0076] III. Precipitate the second mixed solution obtained in step II in a hydrochloric acid solution with a pH of 1.5, collect the precipitate, dissolve the precipitate in N,N-dimethylformamide, and then precipitate it again in a hydrochloric acid aqueous solution with a pH of 1.5, repeat the above process 3 times, and then dialyze it with a dialysis bag with a molecular weight cutoff of 3500Da, first dialyze and purify it in N,N-dimethylformamide solution for 75 hours, and then dialyze and purify it in deionized water for 75 hours, replace the dialyzate every 8 hours, and then vacuum dry it to obtain P powder;

[0077] (1-2) Configuration of P solution

[0078] According to the volume ratio of acetone to anhydrous ethanol being 4:1, acetone and anhydrous ethanol were mixed evenly, and then the P powder was added to prepare a P solution with a concentration of 1 g / ml;

[0079] (2) Preparation of modified PET

[0080] The PET fiber is immersed in a 30% ethanol solution, and ultrasonically treated in an ultrasonic cleaner at an ultrasonic power of 120 Hz for 45 min, and then dried. The dried PET fiber is immersed in the P solution obtained in step (1), and 5 parts by weight of sodium periodate is added. The mixture is stirred for reaction for 2 h, and then vacuum dried at 45° C. for 12 h, the supernatant is poured out, and then dried at 120° C. for 2 h to obtain a modified PET.

[0081] (3) Preparation of antibacterial absorbent core

[0082] (3-1) The modified PET obtained in step (2) is subjected to a twisting treatment to obtain a modified PET fiber having a double helix structure, and then the modified PET fiber is controlled by auxiliary airflow to form a single row with a volume showing a large-small-large structure from top to bottom, wherein the twisting treatment is: using an air jet spinning machine to achieve twisting by high-speed airflow, and the twist is 4500 T·m -1 , the main air flow velocity is 200m / s, the auxiliary air flow velocity is 50m / s, the shape of the modified PET fiber is wavy, the lower layer of non-woven fabric is unrolled and conveyed, and glue is applied on the upper surface of the lower layer of non-woven fabric;

[0083] (3-2) mixing the SAP and the modified PET fiber, adsorbing, conveying, and forming the mixture under negative pressure, and then compounding the mixture onto the surface of the lower non-woven fabric;

[0084] (3-3) unwinding and conveying the upper non-woven fabric, applying glue to the lower surface of the upper non-woven fabric, and then compounding the upper non-woven fabric to the product in step (3-2), and obtaining the antibacterial absorbent core after cutting.

[0085] The antibacterial absorption core comprises a lower non-woven fabric layer, a SAP and modified PET fiber mixture layer, a sizing layer and an upper non-woven fabric layer which are stacked in sequence from bottom to top; wherein the SAP and modified PET fiber mixture layer is obtained by negative pressure adsorption, transportation and molding of SAP and modified PET fibers, and the modified PET fibers comprise the following raw materials: acetone, anhydrous ethanol, PET fibers, sodium periodate, dopamine hydrochloride, N,N-dimethylformamide, propylene glycol methyl ether, silver ammonia solution, azodiol enamine, hydrochloric acid, N,N-dimethylformamide and deionized water;

[0086] The modified PET fiber has a double helix structure, and the modified PET fiber forms a single row with a volume of large-small-large from top to bottom. The SAP is distributed in a staggered manner between the upper and lower adjacent layers of the double helix structure, and the modified PET fiber is wavy in shape.

[0087] Example 4

[0088] The modified PET fiber prepared in Example 1 was combed into a web by a non-woven fabric machine, and then made into a modified PET non-woven fabric by a hot air process.

[0089] Example 5

[0090] The modified PET fiber prepared in Example 2 was taken, combed into a web by a non-woven fabric machine, and then made into a modified PET non-woven fabric by a hot air process.

[0091] Example 6

[0092] The modified PET fiber prepared in Example 3 was combed into a web by a non-woven fabric machine, and then made into a modified PET non-woven fabric by a hot air process.

[0093] Comparative Example 1

[0094] The PET fiber was immersed in an antibacterial finishing liquid for 60 minutes, wherein the antibacterial finishing liquid included the following raw materials in parts by weight: 30 parts by weight of silver nitrate and 1000 parts of deionized water; the PET fiber was then dried at 60°C for 2 minutes, and then the PET fiber was combed into a web by a non-woven fabric machine, and a dissolvable antibacterial non-woven fabric was made by a hot air process.

[0095] Comparative Example 2

[0096] The PET fiber was immersed in an antibacterial finishing liquid for 60 minutes, wherein the antibacterial finishing liquid included the following raw materials in parts by weight: 50 parts by weight of silver nitrate and 1000 parts of deionized water; the PET fiber was then dried at 60°C for 2 minutes, and then the PET fiber was combed into a web by a non-woven fabric machine, and a dissolvable antibacterial non-woven fabric was made by a hot air process.

[0097] Comparative Example 3

[0098] The PET fiber was immersed in an antibacterial finishing liquid for 60 minutes, wherein the antibacterial finishing liquid included the following raw materials in parts by weight: 80 parts by weight of silver nitrate and 1000 parts of deionized water; the PET fiber was then dried at 60°C for 2 minutes, and then the PET fiber was combed into a web by a non-woven fabric machine, and a dissolvable antibacterial non-woven fabric was made by a hot air process.

[0099] Comparative Example 4

[0100] Take 30 parts by weight of PET particles and 30 parts by weight of silver ions, melt the PET particles and then add the silver ions, stir evenly with a stirrer to make an antibacterial material masterbatch, melt the antibacterial material masterbatch and the PET particles in a weight ratio of 3:97, stir evenly with a stirrer, draw them into antibacterial fibers with a fiber drawing machine, comb the antibacterial fibers into a net with a non-woven fabric machine, and then make them into a non-dissolvable antibacterial non-woven fabric through a hot air process.

[0101] Comparative Example 5

[0102] Take 30 parts by weight of PET particles and 30 parts by weight of silver ions, melt the PET particles and then add the silver ions, stir evenly with a stirrer to make an antibacterial material masterbatch, melt the antibacterial material masterbatch and the PET particles in a weight ratio of 1:9, stir evenly with a stirrer, draw them into antibacterial fibers with a fiber drawing machine, comb the antibacterial fibers into a net with a non-woven fabric machine, and then make them into a non-dissolvable antibacterial non-woven fabric through a hot air process.

[0103] Comparative Example 6

[0104] Take 30 parts by weight of PET particles and 30 parts by weight of silver ions, melt the PET particles, add the silver ions, stir evenly with a stirrer to make an antibacterial material masterbatch, melt the antibacterial material masterbatch and the PET particles in a weight ratio of 1:4, stir evenly with a stirrer, draw them into antibacterial fibers with a fiber drawing machine, comb the antibacterial fibers into a net with a non-woven fabric machine, and then make them into a non-dissolvable antibacterial non-woven fabric through a hot air process.

[0105] The test data of Examples 4 to 6 and Comparative Examples 1 to 6 are shown in Table 1. Among them, the antibacterial rate of Escherichia coli is greater than 26%, and the product has an antibacterial effect; the cell viability value is greater than 70%, and the product has no cytotoxicity.

[0106] Table 1

[0107]

[0108] It can be seen from Table 1 that the antibacterial rate of the modified PET non-woven fabrics prepared according to the technical solution of the present application reached more than 99.6%, with good antibacterial effect, good cell activity, and mild and non-irritating to the human body.

[0109] It can be seen from Comparative Examples 1 to 3 that the cell activity of the dissolution antibacterial non-woven fabric is up to 60%, while the antibacterial rate is only 59.5% at this time; by increasing the silver ion content in the antibacterial finishing liquid, the antibacterial rate is increased to 72.3%, and the cell activity is reduced to 53%; when the antibacterial rate is increased to 91.5%, the cell activity is reduced to 33%, and the product is cytotoxic, indicating that the method of coating the silver ion antibacterial finishing agent after the fiber material is formed has greater cytotoxicity.

[0110] It can be seen from Comparative Examples 4 to 6 that the cell activity of the non-dissolving antibacterial non-woven fabric is as high as 93%, but the antibacterial rate is only 3% at this time, and the product has no antibacterial effect; increasing the content of antibacterial material masterbatch in PET particles, the antibacterial rate increases to 13%, the cell activity decreases to 80%, and the product has no antibacterial effect; when the antibacterial rate increases to 30%, the cell activity decreases to 59%, and the product has a certain antibacterial effect, but the product is cytotoxic, indicating that the silver ions cannot be fully exerted by encapsulating the fibers, and the antibacterial effect is poor.

[0111] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.

Claims

1. An antibacterial absorbent core, characterized in that: The invention comprises a lower non-woven fabric layer, a SAP and modified PET fiber mixture layer, a sizing layer and an upper non-woven fabric layer which are stacked in sequence from bottom to top; wherein the SAP and modified PET fiber mixture layer is obtained by negative pressure adsorption, conveying and molding of SAP and modified PET fibers, and the modified PET fibers comprise the following raw materials: acetone, anhydrous ethanol, PET fibers, sodium periodate, dopamine hydrochloride, N,N-dimethylformamide, propylene glycol methyl ether, silver ammonia solution, azodiol enamine, hydrochloric acid, N,N-dimethylformamide and deionized water.

2. The antibacterial absorbent core according to claim 1, characterized in that: The modified PET fiber has a double helix structure.

3. The antibacterial absorbent core according to claim 1, characterized in that: The modified PET fibers form a single row with a volume showing a structure of large-small-large from top to bottom.

4. The antibacterial absorbent core according to claim 1, characterized in that: The SAP is distributed in a staggered manner between the upper and lower adjacent layers of the double helix structure.

5. The antibacterial absorbent core according to claim 1, characterized in that: The modified PET fiber is wavy in shape.

6. A method for preparing an antibacterial absorbent core, characterized in that: The following steps are involved: S1. Preparation of P solution: Mix acetone and anhydrous ethanol evenly in a volume ratio of 3-4:1, then add P powder to prepare a P solution with a concentration of 0.1-1 g / ml; S2, preparation of modified PET: immerse PET fiber in an ethanol solution with a concentration of 30-45%, ultrasonically treat for 30-45 minutes and then dry, then immerse the dried PET fiber in the P solution obtained in step S1, add 1-5 parts by weight of sodium periodate, stir to react for 1-2 hours, then vacuum dry at 40-45°C for 10-12 hours, pour out the supernatant, and then dry at 100-120°C for 1-2 hours to obtain modified PET; S3. Preparation of antibacterial absorption core: a. The modified PET obtained in step S2 is twisted to obtain modified PET fibers with a double helix structure, and then the modified PET fibers are arranged in a single row with a volume of large-small-large from top to bottom through auxiliary airflow control, the lower non-woven fabric is unwound and transported, and glue is applied on the upper surface of the lower non-woven fabric; b. Mixing the SAP and the modified PET fibers, adsorbing, conveying, and forming the mixture under negative pressure, and then compounding the mixture onto the surface of the lower non-woven fabric; c. unwinding and conveying the upper non-woven fabric, applying glue to the lower surface of the upper non-woven fabric, and then laminating the upper non-woven fabric to the product in step b, and obtaining the antibacterial absorption core after cutting; Wherein, the preparation method of the P powder is: I. Under the protection of high-purity nitrogen, dopamine hydrochloride is added to N, N-dimethylformamide and propylene glycol methyl ether in a solid-liquid ratio of 3-5:20:20, and the mixture is uniformly stirred for 1-2 hours to fully dissolve the dopamine hydrochloride to obtain a first mixed solution; II. Add 1-3 parts by weight of silver ammonia solution to the first mixed solution obtained in step I, raise the temperature to 60-70° C., then add 10-15 parts by weight of azodiol enamine, raise the temperature to 100-120° C., and react at a constant temperature for 48-50 hours. After the reaction is completed, a second mixed solution is obtained; III. Precipitate the second mixed solution obtained in step II in a hydrochloric acid solution with a pH of 1-1.5, collect the precipitate, dissolve the precipitate in N,N-dimethylformamide, and then precipitate it again in a hydrochloric acid aqueous solution with a pH of 1-1.5, repeat the above process 2-3 times, and then dialyze it with a dialysis bag with a molecular weight cutoff of 3000-3500Da, and then vacuum dry it to obtain P powder.

7. The method for preparing an antibacterial absorbent core according to claim 1, characterized in that: The dialysis treatment is as follows: firstly, dialysis purification is performed in N,N-dimethylformamide solution for 72-75 hours, and then, dialysis purification is performed in deionized water for 72-75 hours, and the dialysate is replaced every 6-8 hours.

8. The method for preparing an antibacterial absorbent core according to claim 1, characterized in that: The twisting process is: using a jet spinning machine to achieve twisting by high-speed airflow, with a twist of 2500-4500 T·m -1 , the main air flow speed is 50-200m / s, and the auxiliary air flow speed is 10-50m / s.

9. The method for preparing an antibacterial absorbent core according to claim 1, characterized in that: The ultrasonic treatment is carried out in an ultrasonic cleaner with an ultrasonic power of 100-120 Hz.

Citation Information

Patent Citations

  • Preparation method of high-water-absorbing resin with broad-spectrum antibacterial property

    CN107383728A

  • Antibacterial dressing, and preparation method and use thereof

    CN109069687A

  • Antibacterial anti-loosening coating for titanium and titanium alloy implant materials

    CN114159620A

  • Composite non-woven fabric with high absorption performance and preparation method thereof

    CN117758443A

  • Antibacterial dressing, and preparation method and use thereof

    WO2017197542A1